Effects of temperature change on elastic behavior of steel beams with semi-rigid connections - Cai, Jian-guo; Feng, Jian; Han, Yun-long (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2010)
Based on the nonlinear displacement-strain relationship, the virtual work principle method was used to establish the nonlinear equilibrium equations of steel beams with semi-rigid connections under vertical uniform loads and temperature change. Considering the non-uniform temperature distribution across the thickness of beams, the formulas for stresses and vertical displacements were presented. On the basis of a flowchart for analysis of the numerical example, the effect of temperature change on the elastic behavior of steel beams was investigated. It is found that the maximal stress is mainly influenced by axial temperature change, and the maximal vertical displacement is principally affected by temperature gradients. And the effect of temperature gradients on the maximal vertical displacement decreases with the increase of rotational stiffness of joints. Both the maximal stress and vertical displacement decrease with the increase of rotational stiffness of joints. It can be concluded that the effects of temperature changes and rotational stiffness of joints on the elastic behavior of steel beams are significant. However, the influence of rotational stiffness becomes smaller when the rotational stiffness is larger.